PERENCANAAN DAN PENETAPAN KURIKULUM AL-KHAIRIYAH SECARA NASIONAL - Rahayu Permana; Ahmad Suhaili; Angga Pusaka Hidayat (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
Research on Al-Khairiyah Islamic Boarding School in the field of local curriculum has not been specifically examined. Of course, this is very interesting to describe in the results of education policy research. The Al-Khairiyah Islamic Boarding School has a long journey. It has produced many alumni who can become superior human beings and have an insight into science and technology. The Al-Khairiyah curriculum as a local content that wants to be implemented requires the readiness of the Al-Khairiyah Executive Board. This research aims to see the plans that the Al-Khairiyah Executive Board will implement regarding the Al-Khairiyah curriculum nationally for all Al-Khairiyah branches. This study uses historical methods, namely heuristics, source criticism, interpretation, and historiography. The study results found that the Al-Khairiyah Islamic boarding school should have a curriculum containing Al-Khairiyah knowledge. To support the implementation of the Al-Khairiyah curriculum, writing an Al-Khairiyah book as a learning resource is necessary. In realizing the Al-Khairiyah curriculum, an Upgrade was held on June 17, 2017, as the first step to strengthen the implementation of the Al-Khairiyah curriculum.